Post-Traumatic Growth among Family Caregivers of Cancer Patients and Its Association with Social Support and Hope - Razieh Nouzari; Seyed Saeed Najafi; Marzieh Momennasab (Shiraz University of Medical Sciences, 2019)
Background: Cancer not only is a traumatic experience for the patients, but also can affect the family caregivers. Post-traumatic growth (PTG) refers to positive psychological changes experienced by people as a result of a struggle in dealing with traumatic events in life. Both the patients and their caregivers may experience PTG. The present study aimed to assess the extent of PTG in caregivers of patients with gastrointestinal cancer and to examine the relationship between the PTG dimensions and both the social support (SS) and hope. Methods: The present descriptive correlational study was conducted during May-August 2018 in Shiraz, Iran. The target population included 112 caregivers who visited hospitals affiliated to Shiraz University of Medical Sciences, Shiraz, Iran. Data collection instruments included a demographic information form, post-traumatic growth inventory, social support appraisals scale, and Miller hope scale. The data were analyzed using the SPSS software (version 23.0). Pstatistically significant. Results: The mean score for PTG, hope, and SS was 75.41±16.49, 190.95±24.20, and 89.10±12.84, respectively. A significant positive correlation was found between PTG and both SS (P<0.001, r=0.59) and hope (P<0.001, r=0.70). The results of the multiple regression analysis showed a significant relationship between PTG, SS, and hope (P<0.001). Hope had a higher effect on PTG (ẞ=0.62) compared to SS (ẞ=0.27). Conclusion: The results showed a good level of PTG among the caregivers and the experience of stressful situations positively affected their psychological condition. The positive change was associated with the perceived SS and hope.